Purification and properties of a new DNase activity from KB cells. - Frenkel, G D (1981)
A deoxyribonuclease activity with specificity towards single-stranded DNA has been purified approximately four hundred-fold from KB cells, by chromatography on DEAE-cellulose, phosphocellulose and hydroxylapatite. The last step of the purification results in separation of the enzyme from a DNase activity which has been described previously (Wang, E.C., Furth, J.J. and Rose, J.A., (1978) Biochemistry 17: 544-549). The properties of the new DNase activity are significantly different from those of the enzymes which have previously been identified in these cells. The activity sediments at approximately 7.5S in a glycerol gradient. The DNase activity is optimal at pHs between 6.0 and 6.5. It cleaves DNA endonucleolytically and hydrolyzes single-stranded DNA at about 11 times the rate of double-stranded DNA and at twice the rate of Poly (dA). The activity is moderately sensitive to inhibition by N-ethylmaleimide and is inhibited 80% by 50 mM NaCl. It is stimulated twenty-fold by Mn++ at an optimal concentration of approximately 0.7 mM. It is stimulated by a lesser extent by Mg++, but not by Ca++.